Welfare Effect and Elite Capture in Agricultural Cooperatives Intervention: Evidence from Ethiopian Villages - Dambala Gelo; Edwin Muchapondwa; Abebe Shimeles; Johane Dikgang (Institute of Labor Economics (IZA), 2019)
This paper evaluates the impact of the Purchase 4 Progress (P4P) intervention implemented by World Food Program in Ethiopia on per capita income as well as across sub-social groups. The intervention is intended to improve the market power of smallholder farmers through cooperatives that has the potential to increase the relative farm gate price of agricultural produce, particularly staple crops. Using a semi-parametric difference-in-difference (DID) model, which relaxes the parallel trend assumption, we show that the P4P intervention has raised per capita consumption of smallholders. Estimates of the treatment effect from alternative specifications of our preferred models ranged between Ethiopian Birr (ETB) 188.3 and ETB 248.6 (15.10% and 19.93%). Moreover, our analysis suggests heterogeneous treatment effects related to elite capture within Farmer Organizations. Policy implications are discussed.
Keywords: D23; Q02; D02; 330; P4P; welfare effect; distributional bias; semi-parametric DID